Relationship between Fine Motor Skill and the Use of Gadget in Pre-school Age Children - Sri Indah Yuli Hartati; Sidik Awaludin; Eni Rahmawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: To analyze the relationship between fine motor skill and the use of gadget in pre school age children. Methods: This study used a cross-sectional design. Sampling technique using quota sampling and the sample in this study amounted to 82 pre school age children in  Purwanegara, Banyumas on March-April 2022. The adopted questionnaire used to be measured use of gadgets application and abilities acceptable fine motor be measured using Denver II. Data analyzed univariate and bivariate using Gamma Test. Results: The univariate analysis showed that there were eight respondents (9.8%) with gadgets application in the category low, 13 respondents (15.9%) moderate, and 61 respondents (74.4%) high. Denver II results showed fine motor as much as one respondent (1.2%) in category advance, 24 respondents (29.3%) caution, 56 respondents (68.3%) delayed, and one respondent (1.2%) normal. The Gamma test showed a relationship between fine motor skill and the use of gadget  in pre school age children with a p-value = 0,005 (p value<0.05). Conclusion: There is a significant relationship between fine motor Skill and the use of gadget. Based on these results, periodic developmental screening and nursing interventions are needed to address fine motoric disorders in preschool-aged children who use gadgets, and it is expected that parents will limit the use of gadgets.